Pelatihan Pembuatan Bahan Pembelajaran Interaktif Untuk Meningkatkan Kemampuan Literasi Digital Siswa Dengan Pemanfaatan Aplikasi Edpuzzle Bagi Guru-Guru SMA/SMK di Kecamatan Bekri Lampung Tengah - Imanita, Myristica; Lestari, Nur Indah; Triaristina, Aprilia; Perdana, Yusuf (Universitas Negeri Padang, 2023)
The purpose of this service activity is to improve the quality and competence of teachers through training in making interactive learning materials to improve students' digital literacy skills by utilizing the edpuzzle application. The era of globalization is a challenge in itself for the world of education. Information can easily be obtained through the digital world. For this reason, as a teacher/educator you must immediately adapt to current developments, by taking advantage of advanced technology. In this era of globalization, students must have digital literacy skills, so that students do not make the mistake of carrying out digital literacy activities by opening sources that cannot be accounted for. The problem of students' lack of digital literacy skills is a problem that is often found in our world of education, this condition is also felt by high school/vocational school teachers in Bekri District, Central Lampung. For this reason, teachers must pay attention to this by preparing and making fun interactive digital learning materials in the hope that they can improve students' digital literacy abilities and skills which can certainly influence better student learning outcomes. One of the applications that can be used by teachers is the edpuzzle application. Edpuzzle is a video-based application that all teachers can use to make learning as interesting as possible which makes students feel happy watching videos and reading text or content contained in videos. Apart from that, this application allows teachers to be creative in adding some content/descriptions embedded in the video. The method for implementing this service is socialization, training and evaluation. The resulting target output is the ability of high school/vocational school teachers in Bekri District, Central Lampung in making and designing interactive learning materials to improve students' digital literacy skills.Key words: Keywords: Interactive Learning Materials, digital literacy, Edpuzzle Application